South-Western accounting - Rankin, Howard (Thomson/South-Western, 2006)
South-Western Accounting with QuickBooks Pro 2004 is your real-world accounting software solution. The text with data CD is compatible with the Multicolumn, General Journal, and Advanced Century 21 texts. It teaches students to journalize accounting transactions, post to ledger accounts, and prepare financial statements using QuickBooks Pro software